Medication errors related to high-alert medications in a paediatric university hospital - a cross-sectional study analysing error reporting system data - Sini Kuitunen; Mari Saksa; Justiina Tuomisto; Anna-Riia Holmström (BMC, 2023)
Abstract Background Paediatric patients are prone to medication errors, and only a few studies have explored errors in high-alert medications in children. The present study aimed to investigate the prevalence and nature of medication errors involving high-alert medications and whether high-alert medications are more likely associated with severe patient harm and higher error risk classification compared to other drugs. Methods This study was a cross-sectional report of self-reported medication errors in a paediatric university hospital in 2018-2020. Medication error reports involving high-alert medications were investigated by descriptive quantitative analysis to identify the prevalence of different drugs, Anatomical Therapeutic Chemical groups, administration routes, and the most severe medication errors. Crosstabulation and Pearson Chi-Square (χ2) tests were used to compare the likelihood of more severe consequences to the patient and higher error risk classification between medication errors involving high-alert medications and other drugs. Results Among the reported errors (n = 2,132), approximately one-third (34.8%, n = 743) involved high-alert medications (n = 872). The most common Anatomical Therapeutic Chemical subgroups were blood substitutes and perfusion solutions (B05; n = 345/872, 40%), antineoplastic agents (L01; n = 139/872, 16%), and analgesics (N02; n = 98/872, 11%). The majority of high-alert medications were administered intravenously (n = 636/872, 73%). Moreover, IV preparations were administered via off-label routes (n = 52/872, 6%), such as oral, inhalation and intranasal routes. Any degree of harm (minor, moderate or severe) to the patient and the highest risk classifications (IV-V) were more likely to be associated with medication errors involving high-alert medications (n = 743) when compared to reports involving other drugs (n = 1,389). Conclusions Preventive risk management should be targeted on high-alert medications in paediatric hospital settings. In these actions, the use of intravenous drugs, such as parenteral nutrition, concentrated electrolytes, analgesics and antineoplastic agents, and off-label use of medications should be prioritised. Further research on the root causes of medication errors involving high-alert medications and the effectiveness of safeguards is warranted.